C & C - contraction and convergence of carbon emissions: the economic implications of permit trading - Christoph Böhringer; Heinz Welsch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
In the context of climate protection policy it has been suggested that global CO2 emissions should be reduced significantly (contraction) and that per capita emissions should gradually be equalized across countries (convergence). This paper uses a dynamic multi-region computable general equilibrium model of the world economy to assess the economics of ?Contraction and Convergence? (C&C). In comparing a regime of tradable and non-tradable emission rights for implementing C&C we find that the former allows to reduce long-term costs of abatement in terms of Hicksian equivalent variation in lifetime income by more than 50% percent in comparison with the latter. Under a tradable permit regime some developing countries improve their economic welfare even beyond non-abatement baseline levels. A decomposition of the general equilibrium effects associated with C&C shows that changes in the terms of trade constitute a key determinant of the overall welfare effects.
Keywords: D58; Q4; Q2; 330; climate protection; international equity; emissions trading; economic welfare; computable general equilibrium modeling; Klimaschutz; Kohlendioxid; Luftreinhaltung; Emissionsrechte; Wirtschaftspolitische Wirkungsanalyse; Wohlfahrtseffekt; Allgemeines Gleichgewicht; Welt